Metodologia do ensino de Química com experimentação em sala de aula na Casa Familiar Rural de Senador José Porfírio/PA - FREITAS, Neliel Cardoso de (2021)
Given that one of the difficulties of students in assimilating the content of Chemistry is due to the fact that many consider it a complex discipline. To improve this understanding, the use of “experimentation” becomes a facilitating tool for a better understanding of the chemical concepts studied in the classroom, as it brings students' daily life closer. From this perspective, the present work aimed to understand how experimentation can assist in learning chemistry teaching. Therefore, it is necessary to identify the methodology currently used in chemistry teaching, to analyze the difficulties of students in the use of experimental activities and to use experimentation as an auxiliary tool in chemistry classes. To obtain the data, semi-structured questionnaires were applied to the students in order to collect the necessary information. The results showed that the students of the Rural Family House felt motivated with the experimental classes in chemistry teaching, being this fact detected through the applied questionnaires, winch they considered the experimentation important for the teaching and learning process. We conclude from this work that the use of classroom experimentation contributes to meaningful learning, given that seeing in practice the phenomenon happening is very important for its understanding.